Green Management System Application in Post-Covid-19 Agricultural Business Development in Lampung - Isnaini; Chavid Moyo Jaladri (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2023)
The company plans a green management system to manage the environment in order to prevent or reduce the company’s negative impact on the environment, plan the use of resources from the nearby environment—both the physical and social ones—that can have a positive impact on the company, and calculate ways to process and maintain resources so that they can still be used. afterwards utilized. The Business Performance Assessment Program, or PROPER, and environmental cost accounting are two topics that are relevant to green accounting. By providing rating information to businesses and encouraging those with strong environmental records to embrace clean production practices, this program aims to increase corporate compliance with environmental management standards. The PROPER assessment now includes elements of Life Cycle Assessment (LCA), Eco-innovation, and social innovation. According to the PROPER assessment, there has been a surge in the number of businesses in the gold category over the course of two years (2020–2021). The implementation of PROPER in 2020–2021 also documented the achievement of cost savings through efforts to improve water and energy efficiency, reduce emissions and pollution loads, reduce waste, both B3 and non–B3, and other. The use of green accounting varied during the time the COVID-19 virus was deemed a national calamity and afterwards, according to Sari’s research (2022). The company’s continued existence depends on more than just employing the appropriate strategy to meet the demands of global competitiveness.